Aldosterone-secreting adrenocortical adenoma in children - Gupta Vipul (Journal of Indian Association of Pediatric Surgeons, 2007)
Aldosterone-secreting adrenocortical adenoma is an unusual cause of secondary hypertension in childhood. We describe an eight year-old female child who presented clinically with weakness of lower limbs, headache and hypertension. Thorough clinical, laboratory and radiological evaluations confirmed the diagnosis of hyperaldosteronism due to a left adrenocortical adenoma. Left adrenalectomy after preoperative stabilization resulted in satisfactory recovery. Histopathological examination confirmed the diagnosis of an aldosteronoma. We review our experience with this rare entity and the pertinent literature.